Physical and thermal characterization of graphene oxide modified gelatin‐based thin films. Issue 10 (21st January 2014) - Zadeh, Elham Mohammad; Yu, Aimin; Fu, Li; Dehghan, Masoud; Sbarski, Igor; Harding, Ian
<x xml:space="preserve">Abstract</x> The incorporation of graphene oxide (GO) nanosheets into fish gelatin‐based films and the resulting effect on the structural, mechanical, and thermal properties of the film was investigated. Gelatin films were prepared using a casting method with d‐sorbitol as the plasticizer and carrageenan as the stabilizer. GO nanofillers were dispersed into the gelatin network in different weight percentages. FTIR spectroscopy was used to characterize the molecular structure of gelatin films and revealed that there were no major changes in the functional groups of fish gelatin films after addition of GO and carrageenan. Tensile, differential scanning calorimetery (DSC), and thermo gravimetric analysis (TGA) tests were performed to study the effectiveness of GO nanofillers and the effect of sorbitol and carrageenan on the film properties. Addition of 1 wt% of GO significantly increased the tensile strength and the elongation modulus of the gelatin films (to 44 and 1320 MPa, respectively). This was attributed to the strong interfacial interactions between GO sheets and gelatine molecules. However, increasing the GO percentage to 2 wt% resulted in a considerable decrease in both properties (to 11 and 224 MPa, respectively). This might be due to the agglomeration of GO sheets in the gelatin network. DSC results showed a substantial increase in the Tm of the films as a result of adding carrageenan and GO to the gelatin network. This might be due to the strong combination of helical structure of carrageenan and oxygen containing groups of GO. POLYM. COMPOS., 35:2043–2049, 2014. © 2014 Society of Plastics Engineers